(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
In his scientific and cultural itinerary, Franco Basaglia always criticized the nosographic approach of traditional psychiatry, in the belief that there was an irremediable contradiction between the objectivity of science and the subjectivity of the patient. The debate between the different explanatory models of mental distress is also reflected on the penal discipline of insanity, which straddles empirical knowledge and the constitutional principles of guaranteeing the defendant, and on the tasks of the judge, who is entrusted with the difficult role of gatekeeper of the scientific method.